2015
DOI: 10.1080/19336896.2015.1054601
|View full text |Cite
|
Sign up to set email alerts
|

Familial fatal insomnia with atypical clinical features in a patient with D178N mutation and homozygosity for Met at codon 129 of the prion protein gene

Abstract: (2015) Familial fatal insomnia with atypical clinical features in a patient with D178N mutation and homozygosity for Met at codon 129 of the prion protein gene, Prion, 9:3, 228-235, DOI: 10.1080/19336896.2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…There is no significant gender difference in the incidence of FFI. They both have typical clinical features similar to previous descriptions of FFI [16]. Sleep disturbances, such as insomnia and sleep loss, are the common foremost symptoms of the Chinese FFI patients.…”
Section: Discussionsupporting
confidence: 77%
“…There is no significant gender difference in the incidence of FFI. They both have typical clinical features similar to previous descriptions of FFI [16]. Sleep disturbances, such as insomnia and sleep loss, are the common foremost symptoms of the Chinese FFI patients.…”
Section: Discussionsupporting
confidence: 77%
“…insomnia and valine with familial CJD, 2 although this association may not be universal. 33,34 In our cohort, 28 patients could be unambiguously identified as D178N_cis129M and 5 patients as D178N_cis129V. No differences in mean antibody reactivity were seen between those 2 groups (table 4).…”
Section: Description Of the Cohortmentioning
confidence: 59%
“…Within 6 acquired brain autopsy, 1 neuropathologic examination showed changes that were more reminiscent of forms of sporadic CJD; the remaining 5, the histopathology was typical of FFI. Harder et al,1999 [ 9 ] German 7 patients with D178N, including 5 patients with 129M/M,2 patients with 129M/V 7 genetic diagnosis of FFI, but clinical diagnosis with CJD, FFI, AD, GSS,etc Taniwaki et al,2000 [ 10 ] A Japanese family 3 patients with D178N-129M 3 patients with cerebral ataxia without overt insomnia diagnosed fCJD Dauvilliers et al,2004 [ 22 ] French 1 patient with D178N-129M/M FFI presented with circadian rhythms changes Spacey et al,2004 [ 23 ] A family of Chinese descent 1 patient with D178N-129M/M, 1 patietn genotype unclear 2 patients from this kindred were FFI Zarranz et al,2005 [ 12 ] Spanish (Basque born families) 17 patients carrying D178N-129M 7 out of 17 patients has CJD phenotype Synofzik et al,2009 [ 17 ] A German family all with D178N but 129 codon was not all clear demonstrated 1GSS with D178N-M129V, 2 CJD, 1 FFI, 1 atypical Alzheimer, 1 Freidreich ataxia, 1 brain degeneration, 1 brain softening, 1 asymptomatic member with D178N-129M Saitoh et al,2010 [ 24 ] Japanese 2 patients with D178N-129M/M 1 CJD(D178N-129M/M) phenotype and 1 FFI phenotype(D178N-129M/M) with the same PrP sc ratio glycoform Lin et al,2015 [ 7 ] Chinese 1 patient with D178N-129M 1 CJD phenotype Megelin et al,2017 [ 25 ] A French family …”
Section: Discussionmentioning
confidence: 99%
“…Taniwaki et al,2000 [10] A Japanese family 3 patients with D178N-129M 3 patients with cerebral ataxia without overt insomnia diagnosed fCJD Dauvilliers et al,2004 [22] French 1 patient with D178N-129M/M FFI presented with circadian rhythms changes Spacey et al,2004 [23] A [24] Japanese 2 patients with D178N-129M/M 1 CJD(D178N-129M/M) phenotype and 1 FFI phenotype (D178N-129M/M) with the same PrP sc ratio glycoform Lin et al,2015 [7] Chinese 1 patient with D178N-129M 1 CJD phenotype Megelin et al,2017 [25] A French family…”
Section: All Patients Presented With Ffimentioning
confidence: 99%
See 1 more Smart Citation